Effect of Work-Life Balance and Person-Organization Fit on Organizational Citizenship Behavior through Organizational Commitment on Employees of PT. Baba Rafi Indonesia - Mohammad Arif Andrianto; Majang Palupi (TIJAB (The International Journal of Applied Business), 2023)
Background: Well-managed human resources can be a competitive advantage for organizations. The step to creating competitive resources is organizational citizenship behavior. Organizational citizenship behavior can be obtained for every organization if employees have organizational commitment which is influenced by work-life balance and person-organization fit. Objective: This study aims to examine and analyze the effect of work-life balance and person-organization fit on organizational citizenship behavior through organizational commitment. Method: The research was conducted on employees of PT. Baba Rafi Indonesia located in Sidoarjo, East Java, and the Special Capital Region of Jakarta with a sample of 108 respondents. The analytical tool used is the Partial Least Square (PLS) quantitative method. Results: The results showed that: (1) work-life balance has a significant positive effect on organizational commitment; (2) person-organization fit has a significant positive effect on organizational commitment; (3) work-life balance has a significant positive effect on organizational citizenship behavior; (4) person-organization fit has a significant positive effect on organizational citizenship behavior; (5) organizational commitment has a significant positive effect on organizational citizenship behavior; (6) work-life balance has a significant positive effect on organizational citizenship behavior through organizational commitment; and (7) person-organization fit has a significant positive effect on organizational citizenship behavior through an organizational commitment to employees of PT. Baba Rafi Indonesia. Conclusion: Work-life balance and person-organization fit affect organizational citizenship behavior through an organizational commitment to employees of PT. Baba Rafi Indonesia. Keywords: organizational citizenship behavior; organizational commitment; person-organization fit; work-life balance